3D Preoperative Surgical Planning Software for Anterior Cruciate Ligament Reconstruction - Choi, Jin Hyeok; Lim, Sunghwan; Kim, Youngjun; Lee, Deukhee; Park, Sehyung; Park, Shinhyung; Wang, Joon Ho (2013 13TH INTERNATIONAL CONFERENCE ON CONTROL, AUTOMATION AND SYSTEMS (ICCAS 2013), 2013)
Anterior cruciate ligament (ACL) injury is one of the most common ligament injuries and the risk of that is being increased. Arthroscopic technique is commonly used for ACL reconstruction surgery. The arthroscopic surgery for ACL reconstruction contains arthroscopic examination, tunnel formation, and graft passage and fixation. It is important to make tunnel at the exact planned position. Computer-assisted surgery can improve the accuracy of tunnel placement. The exact planned position can be guided with navigation system during surgery. The preoperative planning data is necessary in advance for the navigation system. The purpose of this paper was to make planning software for navigation system for ACL reconstruction. The software is based on open source library and offers information for preparing the surgery. Furthermore, user can make a plan with patient CT data directly in the 3D space. This planning software included automatic segmentation of femur and tibia from patient CT data, radiographic quadrant method in 3D space, and calculation of tunnel length.